ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE AT DISTRIBUTOR COMPANIES - Abdul Haeba Ramli (Business and Entrepreneurial Review, 2017)
This research was conducted in Jakarta which aims to see the extent to which the consequences that will be caused by job satisfaction and organizational commitment to employee performance. The design of this research is to use a survey method by collecting cross-section data through a questionnaire. The number of respondents used as samples in this study, is as many as 120 employees who work in a Public Distribution company located in DKI Jakarta Province with a simple random sampling method. The data analysis method used in is. Structural Equation Modeling (SEM) used for the design analyzes the data in testing the research hypothesis. The results of the study provide evidence that job satisfaction possessed by employees influences positively and significantly and can increase organizational commitment, high job satisfaction also impacts the high achievement of employee performance, then high organizational commitment turns out to have a positive and significant effect on employee performance.